Peningkatan Kemampuan Orang Tua Dalam Mengendalikan Anak-Anak Untuk Mengakses Konten Pornografi - Saut Pintubipar Saragih; Irene Svinarky; Mesri Silalahi (ASOSIASI IDEBAHASA KEPRI, 2021)
Smartphone and computer are commonly tool that people used in any stage of age including children who needs very strict and tight controlling. These technological devices are used for education, business, or social media purposes. In this community service we concern for the children that could lead them to illegal action during using their smartphones or computers such as visiting pornography websites, visiting piracy or dark websites, and lastly surfing illegal websites. Besides positives useful things of the internet technology, Accessing internet without control and supervision has negative risk too, users will have high possibility chances to access or viewing an adult content or pornography websites by their own purpose or just in coincidence moments. The objective of this program is to bring awareness and transfer the knowledge to all participant (parents) technically about setting up smartphones and computer’s features to optimize the parent controlling. Parents will be teaching how to set up the parental feature in their children account, tracing the websites had visited by their teenage children, activate feture to block application, and limits their access to overused application. At the end of this community service will be able to perform their parental control of their teenagers’ children and avoid them to access the pornography or adult content.